The Role of Medial Prefrontal Cortex in Acupuncture Treatment for Functional Dyspepsia - Teng, Yuke; Yin, Tao; Yang, Yue; Sun, Ruirui; Tian, Zilei; Ma, Peihong; He, Zhaoxuan; Qu, Yuzhu; Huang, Liuyang; Chen, Yuan; Zeng, Fang (Frontiers in Neuroscience, 2022)
Acupuncture is an effective therapy for functional dyspepsia (FD). However, the efficacy of acupuncture in the treatment of FD varies among individuals in clinical practice. This study aimed to reveal the brain response patterns in acupuncture higher response/lower response FD patients. Firstly, we performed a within-group comparison of brain function activity before and after acupuncture treatment in 115 FD patients and analyzed the correlation between brain function activity changes and clinical improvements. Secondly, 115 subjects were divided into the acupuncture higher response group or the lower response group based on the median clinical improvement values. The changes in functional brain activity after acupuncture treatment were investigated in these two groups, respectively. Finally, the identified brain regions associated with the clinical improvements were set as regions of interest (ROI), and the ROI-to-voxel functional connectivity comparisons were also performed in both groups, respectively. The results demonstrated that the functional activities of the left cerebellum inferior, right middle temporal gyrus, and right medial prefrontal cortex (mPFC) were increased, and the left Heschl and right middle cingulate cortex were decreased in 115 FD patients after acupuncture treatment. The functional connectivity changes of mPFC were correlated with improving the Nepean Dyspepsia Symptom Index. The significant increase in mPFC functional activity was also found in acupuncture higher response FD patients but not in lower response FD patients. The functional connectivity between the mPFC and default mode network (DMN) was significantly diminished in the higher response group but not in the lower response group. In conclusion, this study suggested that modulating the functional activity of the mPFC and its connectivity to the DMN may be one of the important mechanisms of acupuncture for treating FD with a higher response.